1966
DOI: 10.1243/pime_proc_1966_181_042_02
|View full text |Cite
|
Sign up to set email alerts
|

Knock in Dual-Fuel Engines

Abstract: The paper describes some aspects of the findings of an investigation which was initiated mainly to obtain a better understanding of the phenomenon of knock under dual-fuel operation and to determine the effect of various operating parameters on the knock-free performance limits and the nature of these limits. Some common gaseous fuels such as methane, propane, ethylene, acetylene, hydrogen and somc of their mixtures were used as the main fuels. A method is suggested to relate changes in the knock-limited power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The work of Karim [3,4] on utilization of gaseous fuel such as methane, propane, acetylene, ethylene and hydrogen in diesel engine reveals that the maximum amount of gas consumption is limited due to the onset of knock. He reported that in dual fuel engines, at low load, when gaseous fuel concentration is low, ignition delay period of the pilot fuel increases and some of the homogeneously dispersed gaseous fuel remains unburned and results in poor performance.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Karim [3,4] on utilization of gaseous fuel such as methane, propane, acetylene, ethylene and hydrogen in diesel engine reveals that the maximum amount of gas consumption is limited due to the onset of knock. He reported that in dual fuel engines, at low load, when gaseous fuel concentration is low, ignition delay period of the pilot fuel increases and some of the homogeneously dispersed gaseous fuel remains unburned and results in poor performance.…”
Section: Introductionmentioning
confidence: 99%
“…Knock is due to an autoignition phenomenon dominated by chemical kinetic reactions of the premixed fuel-air system. Karim et al [21] stated that the occurrence of knock was confined by a relatively weak mixture around 60-80% of the stoichiometric ratio. Their investigation into the effects of changes in various operating parameters such as intake temperature and the quantity and quality of pilot liquid fuel, while using various primary gaseous fuels (propane, methane and hydrogen) has proven that knock was observed mainly caused by autoignition of the gaseous fuelair mixture in the neighbourhood of the ignition points originating from the small pilot liquid fuel sprays.…”
Section: Knock Phenomenamentioning
confidence: 99%
“…From these reports [21][22][23][24][25][26] the cause knock phenomena are still an open subject, especially with the current technology advancement that provides ways to measure or simulates such occurrence. CNG is a high octane fuel, which has the characteristic of resisting low temperature ignition normally associated with knock phenomena.…”
Section: Knock Phenomenamentioning
confidence: 99%
“…Additionally, the auto-ignition temperature of CNG is about 3 times higher, in comparison with regular diesel fuel [10]. These selected factors promote the knocking phenomenon, which can even destroy the engine [5,12]. The application of CNG as a fuel for diesels is limited due to technical barriers.…”
Section: Introductionmentioning
confidence: 99%